Examination of Referral Criteria for Outpatient Palliative Care among Patients with Advanced Cancer - Hui, David (Support Care Cancer, 2019)
BACKGROUND: An international panel achieved consensus on 9 need-based and 2 time-based major referral criteria to identify patients appropriate for outpatient palliative care referral. To better understand the operational characteristics of these criteria, we examined the proportion and timing of patients who met these referral criteria at our Supportive Care Clinic. METHODS: We retrieved data on consecutive patients with advanced cancer who were referred to our Supportive Care Clinic between January 1, 2016 and February 18, 2016. We examined the proportion of patients who met each major criteria and its timing. RESULTS: Among 200 patients (mean age 60, 53% female), the median overall survival from outpatient palliative care referral was 14 (95% confidence interval 9.2, 17.5) months. A majority (n=170, 85%) of patients met at least 1 major criteria; specifically, 28%, 30%, 20% and 8% met 1, 2, 3, and ≥4 criteria, respectively. The most commonly met need-based criteria were severe physical symptoms (n=140, 70%), emotional symptoms (n=36, 18%), decision making needs (n=26, 13%) and brain/leptomeningeal metastases (n=25, 13%). For time-based criteria, 54 (27%) were referred within 3 months of diagnosis of advanced cancer and 63 (32%) after progression from ≥2 lines of palliative systemic therapy. The median duration from patient first meeting any criterion to palliative care referral was 2.4 (interquartile range 0.1, 8.6) months. CONCLUSIONS: Patients were referred early to our palliative care clinic and a vast majority (85%) of them met at least one major criteria. Standardized referral based on these criteria may facilitate even earlier referral.